1985
DOI: 10.1007/bf02138833
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of child rearing and self-concept development during the early adolescent years

Abstract: In order to investigate the relationship between aspects of child rearing and adolescent self-concept, 130 males and females in grades 7, 8, and 9 completed Schaefer's Children's Report of Parental BehaviorInventory (CRPBI) and Coopersmith's Self-Esteem Inventory. Correlations between the Acceptance/Rejection dimension of the CRPBI and the various self-esteem subscores were positive. Correlations between the self-esteem scores and the Psychological Autonomy/Psychological Control dimension of the CRPBI were neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
0
5

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 18 publications
8
58
0
5
Order By: Relevance
“…These young teens may have either failed to develop the skills necessary to express themselves or learned that expressing their opinions is not a worthwhile endeavor. Alternatively, to the extent that parental focus on influence is linked with controlling parenting, these adolescents may be too depressed or anxious to express themselves well or confidently (Barber, Olsen, & Shagle, 1994;Baron & MacGillivray, 1989;Conger, Conger, & Scaramella, 1997;Garber, Robinson, & Valentiner, 1997;Leondari & Kiosseoglou, 2002;Litovsky & Dusek, 1985;Pettit, Laird, Dodge, Bates, & Criss, 2001;Rogers, Buchanan, & Winchel, 2003). Nonetheless, parental focus on observable influence may lead parents down the wrong path and is likely to interfere with the adolescents' ability to function autonomously in close relationships.…”
Section: Discussionmentioning
confidence: 99%
“…These young teens may have either failed to develop the skills necessary to express themselves or learned that expressing their opinions is not a worthwhile endeavor. Alternatively, to the extent that parental focus on influence is linked with controlling parenting, these adolescents may be too depressed or anxious to express themselves well or confidently (Barber, Olsen, & Shagle, 1994;Baron & MacGillivray, 1989;Conger, Conger, & Scaramella, 1997;Garber, Robinson, & Valentiner, 1997;Leondari & Kiosseoglou, 2002;Litovsky & Dusek, 1985;Pettit, Laird, Dodge, Bates, & Criss, 2001;Rogers, Buchanan, & Winchel, 2003). Nonetheless, parental focus on observable influence may lead parents down the wrong path and is likely to interfere with the adolescents' ability to function autonomously in close relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve studies (see Table IV, Part A) examined the association between an "affectionless control" parenting style and low self-esteem, self-worth, or self-criticism among offspring (Brewin et al, 1992;Chambers et al, 2001;Garber & Flynn, 2001;Hall et al, 2004;Koestner et al, 1991;Litovsky & Dusek, 1985;Manian et al, 1998;McCranie & Bass, 1984;McGarvey et al, 1999;Oliver & Paull, 1995;Parker, 1993;Tiggerman, Winefield, Goldney, & Winefield, 1992). All found that reported low parental care and/or high parental control were significantly associated with low self-esteem, self-worth, or selfcriticism among offspring, with effect sizes primarily in the small to moderate range.…”
Section: Mechanisms Underlying the Parenting-mood Disorder Associatiomentioning
confidence: 96%
“…At the other end of the spectrum, those who fail to experience positive parenting are more likely to engage with the delinquency (Simons et al, 1988), less academic achievement (Kim and Rohner, 2002;Priyadharshini and Relton, 2014), suffering from substance abuse (Campo and Rohner, 1992;Montgomery et al, 2008), even lead to career indecision in the future (Guerra and Braungart-Rieker, 1999). Last but not least, less in warmth parenting dimension will lead the children to the lower self-esteem (Berg and Kelly, 1979;Litovsky and Dusek, 1985;Seetha and Vinod, 2011).…”
Section: Problem Statementmentioning
confidence: 99%